Survey on research of mini-drones security - Wei LIU; Bing-wen FENG; Jian WENG (网络与信息安全学报)
With the decreasing of the manufacturing cost and the development of technology, mini-drones are spreading from military and high-end commercial areas to civilian and consumer areas, and they have attracted great interests in recent years. On the one hand, mini-drones bring convenient, and on the other hand, they face with serious security problems. The research status of mini-drones, including the security threats of mini drones, the security attacks from mini drones, the authentication and traceability of mini drones, etc were introduced and analyzed. Finally, the future development of security research in mini-drones was also prospected.